2003
DOI: 10.1046/j.1464-410x.2003.04325.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of vesico‐ureteric reflux: a new algorithm based on parental preference

Abstract: Authors from Rome evaluated parental preference for treatment in children with grade III VUR. Parents were provided with detailed information about the three treatment options: antibiotic treatment, open surgery, endoscopic treatment. Most parents chose endoscopic management; with this in mind, the authors proposed a new treatment algorithm for VUR. OBJECTIVE To assess parental preference (acknowledged in treatment guidelines as important when choosing therapy) about treatments for vesico‐ureteric reflux (VUR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 20 publications
4
39
0
Order By: Relevance
“…4,33 Chertin and Kocherov 34 reviewed the current literature regarding the outcome of endoscopic treatment of VUR using different tissue-augmenting substances, with special emphasis on long-term efficacy. They found that the shortterm results in most series were similar to those reported for open surgery, but they also found a significant shortage of evidence-based literature on long-term follow-up after endoscopic correction of VUR using Deflux.…”
Section: Researchmentioning
confidence: 99%
“…4,33 Chertin and Kocherov 34 reviewed the current literature regarding the outcome of endoscopic treatment of VUR using different tissue-augmenting substances, with special emphasis on long-term efficacy. They found that the shortterm results in most series were similar to those reported for open surgery, but they also found a significant shortage of evidence-based literature on long-term follow-up after endoscopic correction of VUR using Deflux.…”
Section: Researchmentioning
confidence: 99%
“…Thus, only a small proportion of children with VUR would undergo open surgery. A very similar treatment strategy was advocated around the same time by other European authors [Capozza et al 2003]. These recommendations are compatible with parental preference: in a survey, 80% of parents expressed a preference for endoscopic treatment, compared with 5% for antibiotic prophylaxis and 2% for open surgery [Capozza et al 2003].…”
Section: Management Of Vur Based On Multifactorial Assessmentmentioning
confidence: 85%
“…Although large international series have shown its effectiveness in the treatment of VUR [19,20], this treatment modality is not considered in the American Urological Association guidelines [1]. Hence, indications are still not generally agreed upon and its use is mostly based on single institution experience and local care policy [19,20] or on parents' preference [21]. Nevertheless, also for endoscopic treatment, grade of VUR does not seem to be a crucial factor any longer [19,20].…”
Section: Discussionmentioning
confidence: 99%